Vibrational Spectroscopic Studies on the Td-type Clathrates: M(dl-Propylenediamine)M’(CN)4·nG - Bayrak, Celal (Asian Journal of Chemistry, 2010)
In this study, M(dl-propylenediamine)M'(CN)4·nG (M = Mn, M' = Zn or Hg; M = Cd, M' = Hg; 1.25 ≤ n ≤ 1.5; G = thiophene) clathrates of dl-propylenediamine (pn) were prepared and their FT-IR and FT-Raman spectra were investigated. The infrared spectra of the clathrates were recorded in the range 4000-50 cm-1 and FT-Raman spectra of the clathrate (Cd-pn-Hg-Thi) was recorded 4000-50 cm-1 and its fundamental vibrational wavenumbers were obtained.